The Importance of Evaluating Positive Welfare Characteristics and Temperament in Working Therapy Dogs - Miller, Sharmaine L.; Serpell, James A.; Dalton, Kathryn R.; Waite, Kaitlin B.; Morris, Daniel O.; Redding, Laurel E.; Dreschel, Nancy A.; Davis, Meghan F. (Frontiers in Veterinary Science, 2022)
To date, investigations of the welfare of therapy dogs have focused largely on examining physiological and behavioral measures that could indicate if the animal is experiencing stress or distress. However, this approach does not fully address the definition of welfare which is often described as existing on a continuum from negative (or stressful) to positive. With therapy dogs, it would be worth addressing if they experience positive emotional affect while working since the quality and efficacy of animal-assisted interventions for the human recipient is likely to be influenced by the animal's emotional state during the interaction. The purpose of this review is to articulate how objective measurements of the HPA axis and measurements of behavioral observations and standardized questions can be used to evaluate positive welfare in therapy dogs. A potentially relevant indicator of positive welfare is the peripheral concentration of the neurohormone oxytocin, which has been found to increase in systemic circulation within a variety of species during positive social and affiliative contexts, including during human-dog interaction. Oxytocin is also a negative-feedback regulator of the Hypothalamic-Pituitary-Adrenal (HPA) axis, which culminates with the production of the stress hormone cortisol. Cortisol is widely used as a physiological indicator to assess negative welfare states in animals, including therapy dogs. Observable behavior during interactions with humans that may convey enjoyment could provide indicators of positive welfare in dogs such as engagement in play, or human-directed affiliative behaviors including leaning against, nudging, or licking the patient. However, in assessing positive welfare, it is also critical to consider that all animal behavioral displays and physiological responses are dependent on the dog's individual (and breed) temperament. Temperament directly drives how the animal copes and responds to its current physical and social environment, including during stressful situations such as when therapy dogs interact with unfamiliar humans in novel healthcare settings. Coupled with both positive and negative physiological and behavioral welfare indicators, questionnaire data can provide further context to, and enhance interpretations of, therapy dog welfare assessment results. Overall, to date, no studies have measured all of these factors to assess therapy dog welfare.